-3x+26=8

Simple and best practice solution for -3x+26=8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3x+26=8 equation:


Simplifying
-3x + 26 = 8

Reorder the terms:
26 + -3x = 8

Solving
26 + -3x = 8

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-26' to each side of the equation.
26 + -26 + -3x = 8 + -26

Combine like terms: 26 + -26 = 0
0 + -3x = 8 + -26
-3x = 8 + -26

Combine like terms: 8 + -26 = -18
-3x = -18

Divide each side by '-3'.
x = 6

Simplifying
x = 6

See similar equations:

| 5.7q-2.2-5.9q=-1.2q-4.3 | | -5w+3+6w=-1+5 | | 5+4(x-1)=8x | | 7(7c-1)-10=47c+7 | | 5(2c-1)-5=8c+6 | | -2(t+3)=0 | | 0.15*0.15*0.15*0.15*0.15=x | | -11n+8=-9n-4 | | -8y+5=-9y+2 | | -2y-10=5y+39 | | .8b-4=.9b+1 | | 9y-4=7y+2 | | m^2-2m-72=0 | | 70=8(c-4)-7 | | -17x-20=-13x+100 | | 20-5x=13+2x | | 12+4x=6*2x | | .5x-3(12)=53 | | -.4p+2=.2+11 | | -4(3-b)=11b+8 | | 5/6(x)-1/5(x)+4=7/10(x) | | 4x+5x=x | | 3-.75x=.5x | | 0.04(p+1.1)=0 | | 70=8(c-4)-2 | | =50-2m^2 | | 0.8(2p-3)=0.6(p-4) | | -.4p+2=-.2p+11 | | .25x+.33x=14 | | c+3737-4737378=373 | | 5(3-2y)+4=3 | | 7.52=2(3.14)(x) |

Equations solver categories